Maternal and fetal outcome in term labour with meconium stained amniotic fluid (Health Renaissance, 2012)
Introduction: Passage of meconium in utero is a dangerous sign for fetal outcome which influence the decision to deliver as well as the mode of delivery. Methods: This descriptive case control study was carried out in the department of Obstetrics and Gynaecology, Koshi Zonal Hospital from March 2006 to July 2006. A total of 50 women with meconium stained amniotic fluid( MSAF) were studied to identify maternal and fetal outcome and was compared with women with clear amniotic fluid. Results: Normal delivery was significantly higher (58%) in clear liquor group as compared to MSAF group (22%). Cesarean section was more common in MSAF group (66%) where as it was (38%) in the clear liquor group (p=0.005). Low Apgar scores of < 5 at one minute was seen in 48% of MSAF and 6% of clear liquor born babies (p